PENGARUH PENEGAKAN HUKUM, DISKRIMINASI PERPAJAKAN, PEMAHAMAN PERPAJAKAN DAN KEADILAN TERHADAP PENGGELAPAN PAJAK (STUDI EMPIRIS PADA WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA PONDOK AREN) - Sari, Indah Permata; Mudzakir (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze the Influence of Law Enforcement, Tax Discrimination, Tax Understanding and Justice on Tax Evasion (Tax Evasion) where analyzing Individual Taxpayers at KPP Pratama Pondok Aren, South Tangerang. The sample used in this study was 100 Individual Taxpayers at KPP Pratama Pondok Aren, South Tangerang using accidental sampling technique. The data used in this study are primary data in the form of distributing questionnaires to all Individual Taxpayers at KPP Pratama Pondok Aren, South Tangerang who have been used as research samples. Multiple regression method is used as an analysis technique in this study. Analysis of research results using SPSS 25 software. The results of the study indicate that law enforcement, tax discrimination, tax understanding and justice simultaneously affect tax evasion. Law enforcement partially affects tax evasion. Tax discrimination partially does not affect tax evasion. Tax understanding partially affects tax evasion. Justice partially influences tax evasion